Synchronised collaborative design between heterogeneous CAD systems based on web service. (30th June 2008) - Weiping, Li; Zhengqi, Gu; Biao, Deng
An approach to construct a synchronised collaborative design platform upon heterogeneous CAD systems based on client-server architecture is presented in this paper. In the approach, the Neuter Feature Set (NFS), which is defined by object oriented representation, is utilised as an intermediate to achieve synchronised exchange of feature-based CAD models between heterogeneous CAD systems. Before achieving this goal, persistent naming of topological entity must have proper solution. A hybrid topological entity naming mechanism is proposed in this paper. Furthermore, in order to extend the system to web services and application integrating environments, central transfer functionality and components are identified. XML is chosen as the most suitable technology and physical transfer format, and a corresponding functional concept is developed for model processing, transcription and CAD interfacing.